Integrated Web-based Palu City Blood Donor Service Application Model Using ReactJS and ExpressJS - Muhammad Jindan; Hajra Rasmita Ngemba; Syaiful Hendra; Rahmah Laila; Syahrullah Syahrullah (Universitas PGRI Semarang, 2023)
Blood donation is an important activity in the medical world that requires efficient coordination between donors and recipients of blood donations so that blood needs are met. However, the blood donation process still needs to be improved because of the lack of donors and the difficulty of blood recipients to find donors. Using this problem, researchers designed and developed a web application that utilizes ReactJS as a frontend Library and ExpressJS as a backend framework. This application will help donors to register, make donor appointments, and access information related to blood donor activities. Admins can use this application to manage information and send notifications to donors. This research system development method needs analysis, system design, application implementation, and testing and evaluation. This research uses two tests, namely Blackbox and a questionnaire. The result of this research is an application system named Badonordarah that can improve the efficiency and effectiveness of the blood donor service process in Palu City and make it easier for donors and blood recipients to interact